Learning Outcomes and Reading Literacy Improvements through the Android Application "My Biotech" on Biology Technology Innovation Material - Raistanto, Wildan Sa'id Sonda; Sari, Dewi Kartika; Usman, Ali (Biosfer: Jurnal Tadris Biologi, 2023)
This study is a classroom action research conducted at SMA Negeri A Bondowoso, specifically in class XC with a total of 36 students, during the second semester of the academic year 2022/2023. In this research, both quantitative and qualitative data were collected. The results of a questionnaire completed by students and teachers in observation sheets during learning were used to generate quantitative data. Qualitative data was collected through observations and interviews with students and teachers. Data collection techniques include observation and testing. Two colleagues were involved as student activity observers. The results improved significantly between cycles I and II. The results of student activity in asking questions during learning were as high as 45% in cycle I to 49% in cycle II. The increase in reading literacy leads to increased listening skills from 51% in cycle I to 58% in cycle II. The increase in students' posttest results was 71% in cycle I and 84% in cycle II. Finally, according to the results of student responses, students who liked biotechnology material increased their acquisition from 47% in cycle I to 52% in cycle II.ABSTRAK: Penelitian ini adalah penelitian tindakan kelas yang dilaksanakan di SMA Negeri A Bondowoso yaitu pada kelas XC dengan jumlah siswa 36 dan dilakukan pada semester genap tahun ajaran 2022/2023. Jenis data yang digunakan dalam penelitian ini, yaitu data kuantitatif dan data kualitatif. Data Kuantitatif didapat dari hasil angket yang diisi oleh siswa dan guru dalam lembar observasi selama pembelajaran. Data Kualitatif diperoleh dari hasil Observasi dan Wawancara kepada siswa dan guru. Teknik pengumpulan data dengan cara observasi dan tes. Observer aktivitas siswa melibatkan dua orang teman sejawat. Terdapat hasil peningkatan yang signifikan antara siklus I dan siklus II. Pada penilaian aktivitas siswa, Hasil keaktifan siswa dalam bertanya selama pembelajaran pada siklus I sebanyak 45%, selanjutnya dihasilkan peningkatan sebesar 49% pada siklus II.  Kemudian peningkatan dari hasil literasi membaca, pada aspek keterampilan menyimak pada siklus I sebesar 51% menjadi 58% pada siklus II. Peningkatan hasil post test siswa pada siklus I sebesar 71% dan siklus II sebesar 84%.  Terakhir, pada hasil respon siswa, siswa yang menyukai materi bioteknologi mengalami peningkatan dari yang sebelumnya diperoleh sebesar 47% pada siklus I, naik secara signifikan dengan perolehan 52% pada siklus II.